Growth of the Pediatric Skeleton A Primer for Radiologists - Oestreich, Alan Emil (Springer Berlin Heidelberg : Imprint: Springer, 2008)
The book is an organized approach to understanding bone growth and disease. It integrates anatomic and radiologic knowledge of enchondral and membranous bone growth and emphasizes the similarities of the physis and acrophysis in development. While mainly written for trainees in radiology, pediatrics, and orthopedics, it will also be useful to practitioners in these fields. The artwork, jointly produced by artist and author, illustrates the concepts being promulgated. The identification of abnormality is aided by the explanations of the causes in terms of pattern recognition.